The Effect of Mathematical Anxiety and Self-Concept on Mathematical Critical Thingking Abilities Through Self-Efficacy - Weni Wihayningrum; Ettie Rukmigarsari; Yuli Ismi Nahdiyatil Ilmi (Jurnal Pendidikan Matematika Universitas Lampung, 2026)
This study aims to: (1) analyze the influence of mathematical anxiety on the self-efficacy of class VIII students of MTsN 6 Malang; (2) analyze the influence of self-concept on the self-efficacy of class VIII students of MTsN 6 Malang; (3) analyze the influence of mathematical anxiety on the mathematical critical thinking ability of class VIII students of MTsN 6 Malang; (4) analyze the influence of self-concept on the critical thinking ability of class VIII students of MTsN 6 Malang; and (5) analyze the influence of self-efficacy on the critical thinking ability of class VIII students of MTsN 6 Malang. This study uses an ex post facto quantitative approach. The research population was all class VIII students of MTsN 6 Malang consisting of 10 classes, while the research sample was taken using cluster random sampling technique in classes VIII D, VIII E, and VIII G. Data collection was carried out through questionnaires to measure mathematical anxiety, self-concept, and self-efficacy, as well as test questions to measure students' mathematical critical thinking ability. The data were analyzed using path analysis with the help of SPSS 25 and SmartPLS software. The results of the study showed: (1) The direct effect of mathematical anxiety on the self-efficacy of grade VIII students of MTsN 6 Malang was -0.295; (2) The direct effect of self-concept on the self-efficacy of grade VIII students of MTsN 6 Malang was 0.503; (3) The direct effect of mathematical anxiety on the mathematical critical thinking ability of grade VIII students of MTsN 6 Malang was -0.252; (4) The direct effect of self-concept on the mathematical critical thinking ability of grade VIII students of MTsN 6 Malang was 0.213; (5) The direct effect of self-efficacy on the critical thinking ability of grade VIII students of MTsN 6 Malang was 0.603.